An effective software implementation of the space-vector modulation - YOUM, J.-H; KWON, B.-H (IEEE transactions on industrial electronics (1982), 1999)
An effective software implementation of the space-vector modulation (SVM) on the rotating d-q frame is proposed. The conventional SVM algorithm requires complex computations, such as square root and arctangent. The SVM algorithm is further developed to determine directly conduction times of switches without requiring complex computations.